Arrangement and Application of Copyright as an Object of Fiduciary Guarantee in Malang City - Vivin Novida Kusumawati (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the regulation and application of Copyright as an object of fiduciary guarantee, especially in Malang City so that this research can provide benefits to the community, especially the public and bank employees in Malang City to know the rules and forms of implementation of the object of fiduciary guarantee, namely Copyright. In Malang City, no people use the object of fiduciary security in the form of Copyright because the provisions of the legislation have not been firmly and established, and there are several other factors. This study uses empirical juridical research methods, interview and observation approach techniques, and two legal data sets, primary and secondary data. The study results found that the statutory arrangements in Indonesia regulate Copyright as an object of fiduciary guarantee as stipulated in Article 16, Paragraph (3) of Law Number 28 of 2018 concerning Copyright. Still, in practice, it has not been implemented optimally and well because in Malang City, no institution oversees, and the nominal amount is not specified in the laws and regulations in Indonesia.